Leadership for evidence-based practice—Enforcing or enabling implementation?. Issue 1 (February 2020) - Harvey, Gill; Kelly, Janet; Kitson, Alison; Thornton, Karleen; Owen, Vanessa
Abstract: Background: The implementation of research evidence into nursing and midwifery practice and care is inconsistent. Leadership is identified as one of the variables that influences the implementation of evidence-based practice. However, less is known about which type of nursing and midwifery leadership roles are key to enhance implementation, nor the specific strategies that should be used. Aim: To explore how different nursing and midwifery leadership roles enact responsibility for implementing evidence-based practice. Methods: Case study of one metropolitan health network, using a qualitative descriptive methodology. Data collection via semi-structured interviews with fourteen purposively selected nursing and midwifery leaders. Findings: Several sources of knowledge were identified that underpinned efforts to implement evidence-based practice, the most significant of which was policies, procedures and clinical guidelines linked to national and state-level standards. In relation to implementing evidence, two distinct leadership approaches were described: one that was more top-down and formalised to ensure adherence to policies, guidelines and national standards; the other a more enabling, relationship-focused approach to support and facilitate staff to practise in an evidence-based way. A number of barriers to achieving evidence-based practice were identified, in particular an over-reliance on policies and guidelines, which could lead to unquestioning practice, and a lack of time due to the realities of clinical practice and heavy workloads. Discussion: The policy agenda in Australia provides a catalyst for evidence-based nursing and midwifery practice via national quality and safety standards, which inform the development and monitoring of local policies, procedures and clinical guidelines. However, leadership strategies that place too much emphasis on adherence to standards, policies and guidelines, without adequate support and resources to interpret and understand the underlying evidence, can produce unquestioning compliance and rote practice. Conclusions: A combination of managerial and facilitative leadership roles and strategies is needed to achieve complementarity between enforcing and enabling the implementation of evidence in nursing and midwifery practice.